2013
DOI: 10.1155/2013/175056
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measurements of the Human Distal Femur: A Study of the Adult Malay Population

Abstract: The distal femurs of 100 subjects (50 men, 50 women) from the Malay population aged between 19 and 38 years were scanned to measure the anterior-posterior (AP) and medial-lateral (ML) width. The mean AP values were 64.02 ± 3.38 mm and 57.33 ± 3.26 mm for men and women, respectively, and the mean ML values were 74.91 ± 3.52 mm and 64.53 ± 3.07 mm. We compared our data to that published previously for the Chinese and Indian populations. It was found that the Malay population had smaller distal femur than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 15 publications
4
34
2
1
Order By: Relevance
“…The measurements are very high in Greek (Caucasian) population in male as well as females. [3] These measurements were almost similar to other populations of Asia [4,14] but higher than population of West Bengal [17] and Indonesia [2] . The medial condylar anteroposterior distance (MCAPD) in males was 57.49±2.34 mm while in females it was 53.91±2.05) which was significantly higher in male than female (p<0.01).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The measurements are very high in Greek (Caucasian) population in male as well as females. [3] These measurements were almost similar to other populations of Asia [4,14] but higher than population of West Bengal [17] and Indonesia [2] . The medial condylar anteroposterior distance (MCAPD) in males was 57.49±2.34 mm while in females it was 53.91±2.05) which was significantly higher in male than female (p<0.01).…”
Section: Discussionsupporting
confidence: 78%
“…The medial condylar anteroposterior distance (MCAPD) in males was 57.49±2.34 mm while in females it was 53.91±2.05) which was significantly higher in male than female (p<0.01). The lateral condylar anteroposterior distance (LCAPD) in males was 59.02±2.69 mm while in females it was 54.82±2.34 mm which was significantly higher in male than female (p<0.05).These measurements were lower than Greek (Caucasian) [3], Chinese [4] and Malasian [14] populations but higher than Indonesian population [2]. It is found similar to the population of Andhra Pradesh [16] but slightly higher in male and lower in females than population of West Bengal [17].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…When they were compared with Chinese population, they had larger femur aspect ratio (FB Cheng). However, a study conducted in Malaysia based on Malay population showed slightly larger distal femoral size than that in this study, even though it was still smaller compared with Western counterpart (Hussain et al, 2013). This study was expected to be useful for further study in developing knee implant designs for Indonesian mongoloid population.…”
Section: Discussionmentioning
confidence: 46%